Implementasi Evaluasi Lahan untuk Pengembangan Komoditas Tanaman berdasarkan Kesesuaian Agroklimat - Mujiyo Mujiyo; Rahayu Rahayu; Novi Rahmawati Sutopo (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2020)
Research activity is a form of expert service by the Research Group (RG) of